Assessment of occupational burnout among private dental practioners in Bengaluru city -a cross sectional study - Reddy, MayurNath; HL, Shwetha; Mishra, Mayur (Journal of Oral and Dental Sciences, 2017)
Introduction: Dentistry is highly rewarding profession, but it’s very demanding job with high degree of concentration and precision in work. Dentists seem to be prone to professional burnout, anxiety disorders and clinical depression because of the variety of sources of stress encountered throughout the professional career.Objectives: To assess the burnout level and physical exhaustion among private dental practitioners.Materials and methods: A cross sectional study was carried out on private dental practitioners in Bengaluru city. A questionnaire containing 22 items Maslach Burnout Inventory and demographic detail, was administered. The response rates were obtained using a likert scale ranging from 0-6. Analysis for p value, cronbach’s α for each questions (>0.700 = high consistency), frequency and comparison of variables, were done.Results: The study found high level of burnout in 11.3% of participants. It also showed age group of
Keywords: Burnout; Dentists; Physical Exhaustion